Effect of Gallotannoids on the Productive Performance and Stress Index of Broiler Chickens under Stress Conditions - Poungpong , Kanokporn; Sumiyoshi, Eisuke; Bunchasak, Chaiyapoom (International Journal of Poultry Science, 2019)
Background and Objective: This study was designed to investigate the effects of hydrolyzable tannoids (gallotannoids) on the productive performance and stress hormone levels (cortisol) of broilers, from hatching to 42 days of age, under high environmental stresses (i.e. heat stress, high stocking density, dirty litter). Materials and Methods: Two hundred and eighty-eight male broiler chickens (Ross 308 strain) were fed a corn-soybean meal-based diet under high stress conditions. The birds were devided into three groups: (1) control group, (2) group that received synthetic vitamin C at 286 ppm and (3) group that received gallotanoid at 100 ppm. Feed and water were offered ad libitum. Results: Gallotannoids significantly improved body weight gain (BWG) and feed conversion ratio (FCR) compared to the control and synthetic vitamin C groups (p0.05). Conclusion: Results indicate that, at the tested doses and under high stress conditions, gallotannoid supplementation can improve broiler production performance more efficiently than synthetic vitamin C.